Orientasi pasar, pilihan strategi dan peran fungsional akuntansi: Studi pada industri hotel di Sumatera Selatan - Setiawan, Antonius Singgih (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2020)
This study aims to prove the influence of market orientation, strategic choices on the role of accounting functional. The study is conducted with quantitative methods using primary data through a survey of hotel general managers/leaders in the South Sumatra province. A total of 75 questionnaires are distributed to the hotel general managers/leaders. The number of questionnaires used in this study is 66 (88%). Structural Equation Modeling (SEM) Partial Least Squares (PLS) analysis using Warp PLS version 5.0 software is used to test of hypothesis. The results of the study indicate that the market orientation and strategic choices have a positive effect on the role of hotel accounting functional in the South Sumatera province.